TRADISI MINAHASA TERKAIT DENGAN MAKANAN TRADISIONAL - Pamantung, Rina Palisuan (Kajian Linguistik, 2019)
Food is regarded as important aspects of indigenous culture of Minahasa when viewed from various Minahasa cultural relics that still survive today. In addition, specific Minahasan traditional food is associated with social behavior which is very typical for a particular event in the culture, but still rarely written scientifically, especially in the field of linguistics.Empirical evidence shows that there is an ambiguity (overlap) on the appearance of the name ofÂ  typical food Â Â betweenÂ  the party menu which still contains the original culture of Minahasa like Endo wangko 'holy day'Â  or "Pengucapan" with a menu of food Â Â that are commercialized as the name of the food Â as a restaurant menu, innÂ  or hotel, and vendor menu. In other words, Â the typical Minahasa food and beverage as a genuineÂ  MinahasanÂ  culture still appear on the religious function of culture, whereas on the other hand, Minahasan traditional food Â has appeared on the restaurant menu as a regular menu. The main problem in this study can be formulated as â€œHow does the naming system ofÂ  food Â that appears in Minahasa cultural traditions based onÂ  myths or folklore that have symbols and myths value and meaningful functioning as a cultural concept ofÂ  Minahasa?â€. The conclusion is the concept of Minahasan culture especiallyÂ  Minahasan traditional food is a dynamic transformation that can be observed in Minahasan culture through the Minahasan traditional foodÂ  naming system linulut vs non-linulut established or determined by a series of meaning components at the taxonomic hierarchy.Keywords: minahasan traditional food, Minahasan culture.